Design of power stage and controller for DC-DC converter systems using PSPICE - Muhamad, N. D.; Sahid, M. R.; Mohamed Yatim, Abdul Halim; Nik Idris, Nik Rumzi (2005)
A complete set of SPICE-compatible design equations for design buck converter system is developed in this paper. In this approach, the power stage and controller design equations are programmed in PSPICE. For this purpose, an option available in PSPICE called Analog Behavioral Modeling (ABM) is used. In this manner, the parameter of power stage and the component values of the error amplifier can be easily obtained by means of PSPICE bias point analysis. The obtained parameters can be passed to other circuit models to perform frequency response and transient analysis. The methodology of development is presented in details. A design example is included to demonstrate the effectiveness of the proposed approach in designing DC-DC converter systems.